Assume that no denominator equals 0.

(2x-3)^2

= 2x * 2x -3 * -3
= 4x-9(answer)

4 answers

no

(2x-3)^2 means (2x-3)(2x-3) which is
4x^2 - 6x - 6x + 9
= 4x^2 - 12x + 9
wouldn't it be 4x^2 + 12x + 9?
why?

-6 -6 = -12

(you borrow $6 from your mom, and then borrow $6 more, how much do you owe her?)
ok I was thinking about multiplication
Similar Questions
  1. Assume that no denominator equals 0.2+i/1-3i = 2+i/1-3i = (2+i/1-3i) * (1+3i/1+3i) = (2+3i^2)/(1-9i^2) = (2/1) - (1/3i) =
    1. answers icon 1 answer
  2. Assume that no denominator equals 0.5x^3(7x)^2 = 5*7*7+x^3+x^2 = 245x^5(answer)
    1. answers icon 1 answer
  3. Can someone check my answers for the following problems.Simplify. Assume that no denominator equals 0. 1)(7x^2+3x-9)-(-x^2+8x-3)
    1. answers icon 6 answers
  4. Assume that no denominator equals 0.(8y^3+27)/(2xy-10y+3x-15) I don't know how to solve this one.
    1. answers icon 1 answer
more similar questions